A study on exploiting commercial digital games into school context - Panoutsopoulos, H.; Sampson, Demetrios (2012)
Digital game-based learning is a research field within the context of technology-enhanced learning that has attracted significant research interest. Commercial off-the-shelf digital games have the potential to provide concrete learning experiences and allow for drawing links between abstract concepts and real-world situations. The aim of this paper is to provide evidence for the effect of a general-purpose commercial digital game (namely, the “Sims 2-Open for Business”) on the achievement of standard curriculum Mathematics educational objectives as well as genera l educational objectives as defined by standard taxonomies. Furthermore, students’ opinions about their participation in the proposed game-supported educational scenario and potential changes in their attitudes toward math teaching and learning in junior high school are investigated. The results of the conducted research showed that: (i) students engaged in the game-supported educational activities achieved the same results with those who did not, with regard to the subject matter educational objectives, (ii) digital game- supported educational activities resulted in better achievement of the genera l educational objectives, and (iii) no significant differences were observed with regard to students’ attitudes towards math teaching and learning.